1986
DOI: 10.1128/iai.52.2.538-548.1986
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies of Pseudomonas exotoxin A gene

Abstract: A 2.7-kilobase DNA fragment carrying the entire exotoxin A (ETA) structural gene was divided into three nonoverlapping probes. Two probes covering the ETA structural gene were used in colony hybridization experiments to determine whether sequences homologous to the ETA gene could be detected in genera other than Pseudomonas or in Pseudomonas species other than Pseudomonas aeruginosa. The majority of strains examined other than the P. aeruginosa strains failed to react in the colony hybridization assays. Some P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…The reliability and high discriminatory potential of DNA fingerprinting suggest its use in bacteriological epidemiology. In conjunction with sero- [6], phage [13], pyocin typing [14] and the DNA probing of hypervariable genomic sites [15] the genome fingerprinting of P. aeruginosa strains may be employed to investigate outbreaks of nosocomial infection and to aid effective infection control, e.g., in cystic fibrosis, the chronic P. aeruginosa infection of the lungs is primarily responsible for pulmonary deterioration and reduced life expectancy [16]. Using DNA fingerprinting, we were able to detect cross-infection with P. aeruginosa strains among siblings with cystic fibrosis, to monitor the acquisition and genomic variations of strains during the course of the disease, and to follow the spread and transmission of organisms in hospital wards (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…The reliability and high discriminatory potential of DNA fingerprinting suggest its use in bacteriological epidemiology. In conjunction with sero- [6], phage [13], pyocin typing [14] and the DNA probing of hypervariable genomic sites [15] the genome fingerprinting of P. aeruginosa strains may be employed to investigate outbreaks of nosocomial infection and to aid effective infection control, e.g., in cystic fibrosis, the chronic P. aeruginosa infection of the lungs is primarily responsible for pulmonary deterioration and reduced life expectancy [16]. Using DNA fingerprinting, we were able to detect cross-infection with P. aeruginosa strains among siblings with cystic fibrosis, to monitor the acquisition and genomic variations of strains during the course of the disease, and to follow the spread and transmission of organisms in hospital wards (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies of the Pseudomonas exotoxin A gene by Vasil et al [31] concluded that the production of exotoxin A and the presence of the exotoxin A gene are probably limited to P. aeruginosa and is not found in other Pseudomonas spp. Southern hybridization experiments under low, medium and high stringency conditions with an exotoxin A gene probe failed to produce a positive signal with any of 8 B. cepacia strains tested.…”
Section: Extraceilular Virulence Factorsmentioning
confidence: 99%
“…The purified DNA (1-2 jtg) was digested with the restriction endonucleases Bgl II, Sal I and Xho I, electrophoresed through a 0-6% agarose gel and transferred to a nylon membrane (Pall, Dreieich, Federal Republic of Germany) using the Southern method (15). The Escherichia coli plasmid pCMtox (16) was isolated (17) and labelled with biotin-1 1-dUTP (Gibco, Bethesda, USA) by nick translation. In modifications of the original method (13), the whole pCMtox plasmid was used for hybridization.…”
Section: Genotyping Of P Aeruginosamentioning
confidence: 99%